The Effect of Taro Tuber Starch (Colocasia esculenta (L.) schott) Addition to Characteristic of Biodegradable Plastic with PVA Polymer and Calcium Carbonate (CaCO3) Filler - Saraswati, Endah; Syahbanu, Intan; Adhitiyawarman, Adhitiyawarman (Jurnal ILMU DASAR, 2023)
The preparation of biodegradable plastics based on polyvinyl alcohol (PVA)-taro starch as an alternative to synthetic plastics has been conducted. The aim of this research was to identify the effect of taro starch composition on the production of biodegradable plastic and their characteristics in an aquatic environment. The solution casting method was used to produce biodegradable plastic. PVA was dissolved in hot distilled water, and taro starch (0; 0.5; 1.5; 2.5; and 3.5 g) was dissolved in another chamber filled with distilled water, glycerol and citric acid. Both solutions were mixed together and CaCO3 was then added. The mixture was casted on acrylic plates while biodegradable plastic without starch was used as a control. Characteristic of Biodegradable plastic and it’s properties were examined by Fourier Transform Infra Red (FTIR), water uptake, and moisture absorption test. While the biodegrability of the sample were tested in river water media in the laboratory. The results showed that the wave number at 1698-1712 cm-1, indicating that the cross-linking between PVA and the starch occured. Water uptake and moisture absorption tests showed that all of the biodegradable plastic varieties produced were hydrophilic. The biodegradation test showed that the largest degree of decomposition was reached by the PVA-starch 3.5 g variety which was 80.33%. Thus, the more starch on biodegradable plastic, the more biodegradation achieved.